Percepções de professores alfabetizadores do município de Votorantim (SP) sobre o pacto nacional pela alfabetização na idade certa (PNAIC): um estudo de caso - Araujo, Samara Elyza Macedo de (Universidade Federal de São Carlos, 2016)
This study seeks to understand the perceptions of literacy teachers on the proposal for continuing education developed under the National Pact Literacy Age One (PNAIC) in the municipality of Votorantim / SP. The methodological approach to the research was qualitative in nature, with data collection conducted through semi-structured interviews, questionnaires and document analysis. The data were analyzed according to a critical perspective. The formation of the literacy teacher is a concern at the current situation, demanding this professional skills and expertise to train students with a view to meeting the demands of capital. It is considered that the PNAIC is also developed in this perspective, being a punctual and discontinued program that aims to standardize the actions of literacy at the national level, conceiving them as mere executors of tasks. The teachers participating in this study believe that the training received in PNAIC is feasible by allowing the exploitation of their educational practices and changes in their ways of teaching literacy. However, the effective participation of these professionals in the construction and implementation of continuing education proposal of PNAIC is not displayed, and even being objective described by the program, the practice of reflexivity, assume the role of protagonists in their professional development and change agents in contexts in which they operate, yet it is a challenge.
Perceptions of literacy teachers of the Votorantim (SP) municipality on the National Pact of Letracy in the right
Keywords: Pacto Nacional pela Alfabetização na Idade Certa (Brasil); Professores - Formação; Professores alfabetizadores; Teachers - In-service training; Reading teachers; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO